2002
DOI: 10.1136/tc.11.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to environmental tobacco smoke and the development of acute coronary syndromes: the CARDIO2000 case–control study

Abstract: Objective: To investigate the association between environmental tobacco smoke (ETS) exposure (at least 30 minutes a day) and the risk of developing acute coronary syndromes (ACS). Design and setting: The CARDIO2000 is a case-control study which was conducted in Greece from 2000 to 2001. Cases included 847 individuals with a first event of ACS and 1078 cardiovascular disease-free controls. Cases and controls were frequency matched on age (within three years of age), sex, and region. Main outcome measures: ACS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 28 publications
0
44
1
2
Order By: Relevance
“…There was no significant heterogeneity (Pϭ0.1), but we used random-effects model to be conservative. Citations for individual studies are as follows: Steenland et al, 152 Kawachi et al, 153 Humble et al, 154 Hole et al, 155 Garland et al, 156 Hirayama, 157 Butler, 158 Sandler et al, 159 Svndsen et al, 160 He et al, 6 Roselund et al, 26 McElduff et al, 161 Ciruzzi et al, 162 LaVecchia et al, 163 Lee et al, 164 Muscat and Wynder, 165 Jackson, 166 Dobson et al, 167 Pitsavos et al, 24 and Whincup et al 28 …”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no significant heterogeneity (Pϭ0.1), but we used random-effects model to be conservative. Citations for individual studies are as follows: Steenland et al, 152 Kawachi et al, 153 Humble et al, 154 Hole et al, 155 Garland et al, 156 Hirayama, 157 Butler, 158 Sandler et al, 159 Svndsen et al, 160 He et al, 6 Roselund et al, 26 McElduff et al, 161 Ciruzzi et al, 162 LaVecchia et al, 163 Lee et al, 164 Muscat and Wynder, 165 Jackson, 166 Dobson et al, 167 Pitsavos et al, 24 and Whincup et al 28 …”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Six meta-analyses have been published, [3][4][5][6][7]22 all yielding relative risks of heart disease from passive smoking that range between 1.2 and 1.3. Since the last meta-analysis was published, we found 6 new epidemiological studies on the association of passive smoking with heart disease (4 case-control [23][24][25][26] and 2 cohort studies 27,28 ). We excluded 2 23,25 of 3 [23][24][25] case-control reports on the same data set and 1 cohort study because of serious misclassification bias.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…SHS exposure may occur at different locations including home (including childhood exposure and exposure from spouse or other family members), work (occupational exposure), and leisure places (exposure at public places other than work). The exposure intensity or frequency in work places is generally higher than that of at home or leisure places (11), and a previous study has suggested that SHS exposure at work places may have a stronger effect on NSCLC risk than exposure at home or leisure places (12). We hypothesized that SHS exposure is associated with worse survival in NSCLC patients, before and after adjusting for cumulative MSS exposure.…”
mentioning
confidence: 99%
“…Due to public health education and as a result of legislation in several developed countries, exposure to second hand smoke is declining at work and public places but direct marketing to younger populations by tobacco companies has contributed to continued high exposure among youths (49)(50)(51)(52). The intensity or frequency of exposure in work places has been noted to be generally higher than that of at home or leisure places (53), and results from a previous study has suggested that SHS exposure at work places may have a stronger effect on NSCLC risk than exposure at home or at leisure places (54).…”
Section: Introductionmentioning
confidence: 98%